Coronary artery intimal thickening and ventricular dynamics in pediatric heart transplant recipients. (5th September 2018) - Cote, Anita T.; Hosking, Martin; Voss, Christine; Human, Derek G; Sandor, George G. S.; Harris, Kevin C.
Abstract: Objective: Pediatric heart transplant recipients are at risk of posttransplant coronary artery disease known as cardiac allograft vasculopathy (CAV), and also may develop diastolic dysfunction. As CAV begins with a process of progressive intimal thickening, these occult diffuse changes may be detected using optical coherence tomography (OCT). We hypothesized that the development of CAV, as identified via OCT, may be a mechanism of declining ventricular function. Accordingly, the purpose of this study was to assess coronary artery intimal thickening and LV strain in children who have undergone heart transplantation. Methods: In 17 children, we analyzed OCT images for coronary intima and media thickness, and cross‐sectional area (CSA). We also performed speckle tracking imaging (STI) of the LV to determine longitudinal strain and strain rate, in addition to standard echocardiographic measures. Results: Longitudinal diastolic strain rate was associated with maximum intima thickness ( r = −.497, P = .042), intima CSA, ( r = −.489, P = .047), maximum media thickness ( r = −.503, P = .039), and media CSA ( r = −.614, P = .009). The intima maximum thickness, intima/media, and intima/lumen ratios were associated with stroke volume index (Std. β = −0.487, P = .023 and Std. β = −0.488, P = .022, respectively). Conclusions: These findings suggest coronary artery intimal thickening may be mechanistically linked to changes in ventricular function following cardiac transplantation.